Extended emission wavelength of random dye lasers by exploiting radiative and non-radiative energy transfer - Wan Ismail W.Z.; Goldys E.M.; Dawes J.M. (Springer Verlag, 2024)
We demonstrate long-wavelength operation (>700nm) of random dye lasers (using a methylene blue dye) with the addition of rhodamine 6G and titania, enabled by radiative and non-radiative energy transfer. The pump energy is efficiently absorbed and transferred to the acceptors, to support lasing in random dye lasers in the near infrared. The optimum random laser performance with the highest emission intensity and the lowest lasing threshold was achieved for a concentration of methylene blue as the acceptor equal to 6 the concentration of rhodamine 6G (donor). Excessive levels of methylene blue increased the lasing threshold and broadened the methylene blue emission linewidth due to dye quenching from re-absorption. This is due to competition between the donor emission and energy transfer and between absorption loss and fluorescence quenching. The radiative and non-radiative energy transfer is analyzed as a function of the acceptor concentration and pump energy density, with consideration of the spectral overlap. The dependence of the radiative and non-radiative transfer efficiency on the acceptor concentration is obtained, and the energy transfer parameters, including the radiative and non-radiative energy transfer rate constants (KR and KNR), are investigated using SternVolmer analysis. The analysis indicates that radiative energy transfer is the dominant energy transfer mechanism in this system. 2016, Springer-Verlag Berlin Heidelberg.